IMPACT OF E-TRADE ON GLOBALIZATION CHANGES IN THE WORLD AND UKRAINE - Gamova , Iryna (Bulletin of Taras Shevchenko National University of Kyiv. Economics, 2023)
The article examines different approaches of scientists to the impact of e-commerce on globalization transformations in the world and in Ukraine. E-commerce has become a primary factor in accelerating the process of globalization. The increase in the value of goods exported and imported around the world reflects the development of international trade, globalization, and technological progress. The trends of world economic development were analyzed and the correlation between economic growth and trade was revealed. The author studied the dynamics of the share of retail e-commerce by region and analyzed the regional share of e-commerce in retail. Countries with fast growth in e-commerce differ from the list of e-commerce leaders, which indicates that the markets are oversaturated with goods, that is, supply outweighs demand. An analysis of countries with rapid growth in e-commerce, the level of Internet penetration, and the number of e-users was carried out. Attention is paid to the examination of the market capitalization of the leading e-commerce enterprises with capitalization around the world, and the largest e-commerce enterprises in the world and Ukraine are studied, and their influence on globalization transformations is established. It was revealed that the world’s strongest economies and the world’s largest e-enterprises are not always open to globalization transformations. A slowdown in economic growth means a decrease in the demand for imports of goods and services, as well as a weakening of the supply of capital. e-commerce will develop in the future according to two alternatives: the closeness of countries and stagnation of global economic institutions and unions with weakening of balanced economic growth and development; the regulation and expansion of free trade with increased competitiveness and the formation of a new structure of the world economy, which will ensure stable, balanced development.